Analysis of changes in growth parameters and primary root architecture of Arabidopsis thaliana under the influence of copper and iron oxide nanoparticles - Aliakseyeva, Maryia I.; Muravitskaya, Anna O.; Mackievic, Viera S.; Samokhina, Veranika V.; Tarima, Veranika V.; Muchinskaya, Palina A.; Pshybytko, Natalia L.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2025)
Nanoparticles containing copper and iron oxides are increasingly used in agriculture as nanofertilisers. Despite this, the question of their toxicity for plant organism remains unresolved. To address this, it is necessary to conduct researches on model objects under standardised conditions. This paper presented the results of experiments on the effect of copper oxide nanoparticles (here and further – CuO-NPs) and iron oxide nanoparticles (here and further – Fe3O4-NPs) on the growth parameters and primary root architecture of Arabidopsis thaliana (L.) Heynh. in vertical culture in vitro. Treatment with CuO-NPs at concentrations of 10 and 30 mg/L and Fe3O4-NPs at concentrations of 30; 100 and 300 mg/L stimulated the primary root growth of A. thaliana, while application of CuO-NPs at concentrations above 100 mg/L and Fe3O4-NPs at concentrations above 300 mg/L inhibited this process. It was found that CuO-NPs exhibit lower toxicity than the ionic form Cu2+ (CuCl2) introduced into the gel medium at the same concentrations as the mentioned nanoparticles. Treatment with the studied nanoparticles led to a modification of the primary root architecture: the diameter of the primary root in the mature epidermis zone, the length of the elongation zone of this organ and its diameter in the division zone decreased after the application of CuO-NPs and increased after treatment with Fe3O4-NPs. It was concluded that CuO-NPs and Fe3O4-NPs used for the production of nanofertilisers exhibit relatively low toxicity, while Fe3O4-NPs demonstrate a strong root-stimulating effect under the treatment at a wide range of concentrations.